تعليم القرآن الكريم وعلومه للأطفال - بوروبة, محمد لمين (University of Eloued جامعة الوادي, 2019)
هذا الدراسة تتناول الحديث عن تعليم القرآن وعلومه للأطفال وتبين مدى أهميته وأثره عليهم في حياتهم، مع ذكر آراء العلماء فيه، وبيان اختلافهم في هل يُبدأ في أول عملية تعليم الأطفال بتعلم القرآن الكريم وحده أم لا؟ وهل يُقرنُ في تعليمه معه غيره من علوم الأخرى؟ بالإضافة إلى ذكر بيان طرق تعليم القرآن وعلومه للأطفال في الكتاتيب والمحاضر والزوايا والمدارس القرآنية، مع ذكر أهم الوسائل المعتمدة في ذلك. وتختم الدراسة بذكر كيفية النهوض والرقي به وذلك من خلال ذكر عدة نصائح وتوجيهات قد تساهم وتساعد في النهوض والرقي بعملية تعليم القرآن وعلومه للأطفال في عصرنا الحاضر. The summry • The present study is entitled in « Teaching the Holy Quran and its sciences to children : its importance , impact , scholars opinions , approaches ,tools and how to progress and develop withit » • This paper deals with teaching the Holy Quran and its sciences for little children and kids , and shows the importance of it and its impact on them .In addition to set the different views and oppinions of scholars twards teaching it separately or being joined with other sciences. • This study also puts the light on how to teach the Holy Quran to children in «Kattatib » , « Zawya » , and « Quranic Schools » ,by setting the most important tools uesed in teaching. • The study finishes by mentionning how to develop it through giving some advice and recommendations that can lead to inhance and develop the way of teaching the Holy Quran and its sciences to children in nowadays.
أهميته، وأساليبه، وأثره، وكيفية الرقي به
مقال بمجلة الشهاب
Keywords: القرآن الكريم ؛ تعليم الأطفال؛ الرقية; The Holy Quran; Educating Children; Al-Ruqyah